Aid in the Aftermath of Hurricane Katrina: Inferences of Secondary Emotions and Intergroup Helping (Group Processes & Intergroup Relations, 2011)
Abstract This research examines inferences about the emotional states of ingroup and outgroup victims after a natural disaster, and whether these inferences predict intergroup helping. Two weeks after Hurricane Katrina struck the southern United States, White and non-White participants were asked to infer the emotional states of an individualized Black or White victim, and were asked to report their intentions to help such victims. Overall, participants believed that an outgroup victim experienced fewer secondary, `uniquely human? emotions (e.g. anguish, mourning, remorse) than an ingroup victim. The extent to which participants did infer secondary emotions about outgroup victims, however, predicted their helping intentions; in other words, those participants who did not dehumanize outgroup victims were the individuals most likely to report intentions to volunteer for hurricane relief efforts. This investigation extends prior research by: (1) demonstrating infraglobalhumanization of individualized outgroup members (as opposed to aggregated outgroups); (2) examining infrahumanization via inferred emotional states (as opposed to attributions of emotions as stereotypic traits); and (3) identifying a relationship between infra-humanization of outgroup members and reduced intergroup helping. a-cuddy@kellogg.northwestern.edu (Cuddy, Amy J. C.) Northwestern University - (Cuddy, Amy J. C.) University of Massachusetts - Amherst--> - (Rock, Mindi S.) Harvard Business School - (Norton, Michael I.)